AN OVERVIEW OF THE CRITERIA AND DIMENSIONS OF THE MOST IMPORTANT ARAB MODELS FOR EXCELLENCE MANAGEMENT IN BUSINESS ORGANIZATIONS - Boumediene, Mechta; Fatima Zohra, Mahdid; Nourelhouda, Bahlouli; Zaidi , Belkasmi (The journal of contemporary issues in business and government, 2024)
There exists a set of global models that have focused primarily on excellence and its management, each relying on different criteria and principles. These models addressing excellence management vary both at the global and Arab levels. Clarifying the underlying principles and governing values of these models is of utmost importance. This clarification aids organizations in ensuring the application of excellence standards, measuring the level of performance or service provided. Hence, the significance of this study emerges, aiming to present some models and awards of excellence in Arab countries, highlighting their key features and dimensions, and attempting to compare them with global excellence management models. The study concludes that both global and Arab excellence models share many dimensions and criteria through which excellence is managed within organizations, as these organizations operate globally within the framework of openness to the global market.